THE DEVELOPMENT OF PROGRAM LOGIC CONTROL (PLC) TRAINER MEDIA IN VOCATIONAL HIGH SCHOOLS - Silaban, Rafles Asmawati; Rizal, Fahmi (Journal of Education Research and Evaluation, 2020)
This study aimed to develop the Program Logic Control ( PLC ) media. The validity, practicalities, and effectiveness, can be used as a media of teaching in schools on subjects IML. The method used was Research and Development (R&D) with the 4-D model of developing procedure. The subjects in this study were students of SMK Negeri 5 Batam, the technical data analysis obtained from 5 experts. Analysis of the data used to measure the validity, practicality, and effectiveness by looking at the difference between the average score of learning scores before and after using the trainer with Gain Score and Standard Deviation. The results of the study met the instructional media qualifications from the assessment of experts with a level of 0.88 stated in the valid category. In practicality based on the teacher's response was 92.00% and on the student, responses were 90.50%. Effectiveness is obtained from the results of the pretest with an average score was 59.63%, from the results of the posttest with an average score of 79.63%, the N-gain of the average student was 0.37 and the standard deviation from N -gain was 0.52. So, PLC trainers are valid, practical, and effective in learning at school. The PLC media trainer can be used in the learning process at school.